Exploring the nematicidal activity of plant extracts for management of Meloidogyne incognita in local cultivars of eggplant (Solanum melongena L.) in Pakistan. (14th December 2021) - Arshad, Usman; Butt, Husnain; Ali, Muhammad Amjad; Jabran, Muhammad; Zahid, Muhammad Salman; Sarfraz, Sohaib
Abstract: In this study, effort was made to manage the root-knot nematode ( Meloidogyne incognita ) by utilising plant extracts. Four plants e.g., Marigold ( Tagetes erecta ), Kanair ( Nerium oleander ), Neem ( Azadirachta indica ) and Auk ( Calotropis procera ) were used to make extracts and check their nematicidal efficacy against M. incognita in four local cultivars (Cluster king, Dilnasheen, Nirrala and Purple Queen) of eggplant in pots. Results revealed that the Marigold exhibited promising results to manage M. incognita egg masses and no. of females (92.3, 89.43%) in Nirrala among all treatments. Moreover, Neem brought about significant results after Marigold in controlling M. incognita egg masses and no. of females (87.96, 85.35%) in Cluster King followed by other plant extracts. Additionally, plant extracts also led to increase the plant upper and lower biomass recorded in Nirrala and Purple Queen. The results demonstrate a potential use of non-chemical control of root-knot nematode with agricultural application.